Pattern of placental alkaline phosphatase (PLAP) expression in human tumors: a tissue microarray study on 12, 381 tumors. (7th August 2021) - Reiswich, Viktor; Gorbokon, Natalia; Luebke, Andreas M; Burandt, Eike; Menz, Anne; Kluth, Martina; Hube‐Magg, Claudia; Wittmer, Corinna; Weidemann, Sören; Fraune, Christoph; Möller, Katharina; Lebok, Patrick; et al.
Abstract: Placental alkaline phosphatase (PLAP) is commonly expressed at high levels in testicular germ cell tumors. PLAP immunohistochemistry (IHC) is thus often used to confirm this diagnosis, especially in cases of putative metastasis. However, other tumors can also express PLAP. To comprehensively determine PLAP expression in normal and tumor tissue, a tissue microarray containing 16, 166 samples from 131 different tumor types and subtypes as well as 608 samples from 76 different normal tissue types was analyzed by IHC. Moderate to strong PLAP positivity was found in 27 (21%) of 131 different tumor types including seminoma (96%), embryonal carcinoma (85%), and yolk sac tumors of the testis (56%); endometrioid carcinoma of the endometrium (28%) and the ovary (20%); gastric adenocarcinoma (22%); serous carcinoma (not otherwise specified) of the ovary (17%) and the uterus (11%); adenocarcinoma of the ampulla of Vater (15%); carcinosarcoma of the ovary (11%) and the uterus (8%); esophageal adenocarcinoma (10%); invasive urothelial carcinoma (4%); cholangiocarcinoma (2%); and adenocarcinoma of the lung (1%). Low‐level PLAP immunostaining, often involving only a small fraction of tumor cells, was seen in 21 additional tumor entities. The clinical significance of PLAP expression may vary between tumor types as high PLAP expression was linked to advanced pathological tumor stage ( p  = 0.0086), nodal metastasis ( p  = 0.0085), and lymphatic ( p  = 0.0007) and blood vessel invasion ( p  = 0.0222) in colorectal cancer, but to low pathological tumor stage in endometrial cancer ( p  = 0.0043). In conclusion, our data identify several tumor entities that can show PLAP expression at comparable levels to testicular germ cell tumors. These tumor entities need to be considered in cases of PLAP‐positive metastasis. Low‐level PLAP expression can be found in various other tumor entities and should generally not be viewed as a strong argument for germ cell neoplasia.